Manajemen Pendidikan dalam Kajian Epistemologi - Yusuf Aditya, Dedy; Nurmantoro, Muh. Aripin; Kamali, Asep Saefullah; Saepul Mustakim, Usep; Indriani, Arina Nur (Metakognisi, 2023)
The purpose of writing this scientific article is to answer several problems including: 1) The definition and meaning of epistemology. 2) the basic concept of education management. 3) the function of education management. 4) Principles or General Principles of Education Management. 5) Organizational Divisions in terms of Education Management Epistemology. The writing of this scientific article uses a literature study or literature study approach by collecting various relevant literature sources. The results of the study show several things including: 1) Epistemology of education is understood in various ways according to the views of Idealism, Realism, Pragmatism and Existentialism. 2) Management functions include planning, organizing, directing, coordinating and controlling 3) Education management is divided into divisions so that the education management function can run effectively and efficiently.